Two new species of Edwardsiana Zachvatkin (Hemiptera: Auchenorrhyncha: Cicadellidae: Typhlocybinae) and an additional newly recorded species from the Korean Peninsula - Oh, Sumin; Kim, Il-Kwon; Jung, Sunghoon (Zootaxa, 2025)
Two new species of the genus Edwardsiana Zachvatkin, E. curvata sp. nov. E. directa sp. nov., and one newly recorded species, E. ishidai (Matsumura, 1932) are described from the Korean Peninsula, and we provide a key to the Korean species.